Gnostic Myth About Salvator Salvatis and Its Elements in F.M. Dostoyevsky's Novel "The Idiot" - Ekaterina V. Moskvina (Достоевский и мировая культура: Филологический журнал, 2018)
In the article the structure of the soteriological myth about Salvator salvatus (the saved Saviour), based on material of the early Christian text “The Hymn of the Pearl” from the “Acts of Thomas” is presented; it is the key to understanding of a number of Gnostic ideas widespread in European and Russian culture. In the myth reflecting the extremely dualistic concept of the world, the idea is that the Savior, who came to release the souls of the chose generation from the captivity of matter, himself needs salvation, since becomes a victim of the world in which he came, so a “hero” appears, sent by the world of Light to save the Savior. Supported by original texts, examine the Gnostic ideologems such as the dualistic vision of the world, the negative understanding of urban topos as the world of material evil, the motive of assimilating the Savior to someone else, the figurative triad of the demiurge-soulSavior, the idea of the chose generation, etc., were considered at the subject and figurative level in the novel “The Idiot”. The article also lists the most obvious sources of some Gnostic elements of the text, for example, the work of Schiller and Shakespeare, Schelling’s philosophy. A detailed analysis proved not only the Gnostic orientation of Dostoevsky’s philosophical thought, not familiar with either the apocryphal “Acts of Thomas”, nor the Nag Hammadi texts found in the 20th century, which gives the right to speak about the originality of Dostoevsky’s philosophy, but also does not exclude the possibility of applying to interpretation of the novel gnostic code.